The haematological consequences of plasmodium vivax malaria after chloroquine treatment with and without primaquine: a WorldWide Antimalarial Resistance Network systematic review and individual patient data meta-analysis - Commons, RJ; Simpson, JA; Thriemer, K; Chu, CS; Douglas, NM; Abreha, T; Alemu, SG; Añez, A; Anstey, NM; Aseffa, A; Assefa, A; Awab, GR; et al. (BioMed Central, 2019)
Background Malaria causes a reduction in haemoglobin that is compounded by primaquine, particularly in patients with glucose-6-phosphate dehydrogenase (G6PD) deficiency. The aim of this study was to determine the relative contributions to red cell loss of malaria and primaquine in patients with uncomplicated Plasmodium vivax. Methods A systematic review identified P. vivax efficacy studies of chloroquine with or without primaquine published between January 2000 and March 2017. Individual patient data were pooled using standardised methodology, and the haematological response versus time was quantified using a multivariable linear mixed effects model with non-linear terms for time. Mean differences in haemoglobin between treatment groups at day of nadir and day 42 were estimated from this model. Results In total, 3421 patients from 29 studies were included: 1692 (49.5%) with normal G6PD status, 1701 (49.7%) with unknown status and 28 (0.8%) deficient or borderline individuals. Of 1975 patients treated with chloroquine alone, the mean haemoglobin fell from 12.22 g/dL [95% CI 11.93, 12.50] on day 0 to a nadir of 11.64 g/dL [11.36, 11.93] on day 2, before rising to 12.88 g/dL [12.60, 13.17] on day 42. In comparison to chloroquine alone, the mean haemoglobin in 1446 patients treated with chloroquine plus primaquine was − 0.13 g/dL [− 0.27, 0.01] lower at day of nadir (p = 0.072), but 0.49 g/dL [0.28, 0.69] higher by day 42 (p < 0.001). On day 42, patients with recurrent parasitaemia had a mean haemoglobin concentration − 0.72 g/dL [− 0.90, − 0.54] lower than patients without recurrence (p < 0.001). Seven days after starting primaquine, G6PD normal patients had a 0.3% (1/389) risk of clinically significant haemolysis (fall in haemoglobin > 25% to < 7 g/dL) and a 1% (4/389) risk of a fall in haemoglobin > 5 g/dL. Conclusions Primaquine has the potential to reduce malaria-related anaemia at day 42 and beyond by preventing recurrent parasitaemia. Its widespread implementation will require accurate diagnosis of G6PD deficiency to reduce the risk of drug-induced haemolysis in vulnerable individuals. Trial registration This trial was registered with PROSPERO: CRD42016053312. The date of the first registration was 23 December 2016.